IN-VITRO REGENERATION AND CALLUS FORMATION FROM DIFFERENT PARTS OF SEEDLING OF MUCUNA PRURIENS BAK A VALUABLE MEDICINAL PLANT - R. K. PANDEY; MEHTA, ANITA; PATEL, SHALINI (The Bioscan, 2007)
Callus proliferation was studied on cotyledon, leaf and stem explant of Mucuna pruriens Bak cultured on Murashige and Skoogs medium (MS) supplemented with 2,4-D, IBA, NAA and BAP alone or in combination. Light brown callus formation was followed by formation of milky white callus on the surface of young excised shoots and leaf tissues of Mucuna pruriens. Sometimes green callus was also observed. Development of root and stem with leaves were investigated from excised stem, leaf and cotyledon tissues.